INFLUENCE OF FINANCING BY FACTORING ON COMPANY’S LIQUIDITY IN BOSNIA AND HERZEGOVINA - Emira Kozarević; Mirela Hodžić (Economic Review)
The economic crisis, which did not leave Bosnia and Herzegovina (BiH) unaffected, and the increasingly present problems with the collection of accounts receivable made the companies in BiH turn to factoring, a modern financial tool that provides liquidity. Very frequently, slow collection of claims may be a problem, especially for small and medium-sized enterprises that have difficulties in accessing short-term loans and in providing collateral for loans and often face the problems of financing liquid capital. Due to all this, factoring is a high-quality instrument for “extinguishing” illiquidity as by cession of claims the company obtains cash in a very short period. This paper aims to establish the importance of factoring as a modern financing tool in keeping liquidity, competitiveness, and export capacities of small and medium-sized enterprises in BiH and to indicate advantages and disadvantages of factoring as a modern form of financing compared to traditional financing forms. Financing by factoring is directly related to the subjects in factoring activities, factoring item as well as to the costs, elements, and risks of factoring. It is therefore very important to accentuate the differences between financing by factoring and by short-term loans.